Pengaruh Ineffective Monitoring, Komitmen Organisasi, Kultur Organisasi, Perilaku Tidak Etis Terhadap Kecenderungan Kecurangan Pelaporan Keuangan - I Gede Prema Utama; Gede Adi Yuniarta (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2020)
This research was conducted to examine the effect of ineffective monitoring, organizational commitment, organizational culture, unethical behavior towards the tendency of fraudulent financial reporting. This study uses numerical analysis of the variables used, therefore using a quantitative approach. The study population was a savings and credit cooperative with an active status in Tabanan District, Tabanan Regency. In this study using a sampling technique that is purposive sampling. Respondents from each savings and loan cooperative amounted to 5 people consisting of managers and managers of the cooperative. So that the total number of samples in this study were 6 KSP x 5 people to 30 people / sample. Data collection techniques in this study are by distributing questionnaires. The data were then analyzed with several analyzes including descriptive statistics, classic assumption tests and multiple regression analysis with the presentation of data assisted by the SPSS 20. The results showed that ineffective monitoring did not affect the tendency of fraudulent financial reporting, organizational commitment did not affect the tendency of fraudulent financial reporting of organizational culture negative effect on the tendency of fraudulent financial reporting, and unethical behavior significantly positive effect on the tendency of fraudulent financial reporting